Innovating for Social Impact: a Business Model Analysis of HDI’s Mobile Game App, Go Nisha Go in India - Shankar, Lalita; Howard, Susan; Delafield, Sylvia; Provodnikova, Anna (Global journal of Business and Integral Security, 2026)
This study explores how the Go Nisha Go (GNG) mobile game leverages digital innovation to empower adolescent girls in India. Using the Business Model Canvas framework, a three-year qualitative case study reveals that GNG’s success stems from its user-centred design, strategic use of mobile technology, and hybrid partnership model. GNG demonstrates the potential of digital solutions for delivering scalable, culturally sensitive, and cost-effective interventions to underserved populations, informing future digital health projects. The study reveals a critical challenge in digital health innovation: balancing traditional grant-making with insights on how new product development strategies and market viability can augment project and program goals. As funding landscapes shift toward market-based solutions, organizations must navigate the complex interplay between mission-driven objectives and fostering scalability and sustainability.